Contemporary conditional cancer‐specific survival rates in surgically treated adrenocortical carcinoma patients: A stage‐specific analysis. Issue 4 (26th November 2022) - Panunzio, Andrea; Barletta, Francesco; Tappero, Stefano; Cano Garcia, Cristina; Piccinelli, Mattia; Incesu, Reha‐Baris; Law, Kyle W.; Tian, Zhe; Tafuri, Alessandro; Tilki, Derya; De Cobelli, Ottavio; Chun, Felix K. H.; et al.
Abstract: Background and Objectives: We examined the effect of disease‐free interval (DFI) duration on cancer‐specific mortality (CSM)‐free survival, otherwise known as the effect of conditional survival, in surgically treated adrenocortical carcinoma (ACC) patients. Methods: Within the Surveillance, Epidemiology, and End Results database (2004−2018), 867 ACC patients treated with adrenalectomy were identified. Conditional survival estimates at 5‐years were assessed based on DFI duration and according to stage at presentation. Separate Cox regression models were fitted at baseline and according to DFI. Results: Overall, 406 (47%), 285 (33%), and 176 (20%) patients were stage I−II, III and IV, respectively. In conditional survival analysis, providing a DFI of 24 months, 5‐year CSM‐free survival at initial diagnosis increased from 66% to 80% in stage I−II, from 35% to 66% in stage III, and from 14% to 36% in stage IV. In multivariable Cox regression models, stage III (hazard ratio [HR]: 2.38;  p  < 0.001) and IV (HR: 4.67;  p  < 0.001) independently predicted higher CSM, relative to stage I−II. The magnitude of this effect decreased over time, providing increasing DFI duration. Conclusions: In surgically treated ACC, survival probabilities increase with longer DFI duration. This improvement is more pronounced in stage III, followed by stages IV and I−II patients, in that order. Survival estimates accounting for DFI may prove valuable in patients counseling.